2018
DOI: 10.1136/bmjopen-2017-016610
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Associated Risk Tool: development and validation of a self-assessment questionnaire to screen for hospitalised patients at risk for drug-related problems

Abstract: IntroductionIdentifying patients with a high risk for drug-related problems (DRPs) might optimise the allocation of targeted pharmaceutical care during the hospital stay and on discharge.ObjectiveTo develop a self-assessment screening tool to identify patients at risk for DRPs and validate the tool regarding feasibility, acceptability and the reliability of the patients’ answers.DesignProspective validation study.SettingTwo mid-sized hospitals (300–400 beds).Participants195 patients, exclusion criteria: under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 38 publications
1
38
0
1
Order By: Relevance
“…Two studies [ 18 , 38 ] did not report the age demographics of the study participants (although participants were adults). The remaining studies were conducted in adult patients (including but not exclusively elderly patients) [ 3 , 20 , 34 , 35 , 36 , 37 , 39 , 40 , 42 ]. The majority of the studies presented either the mean or median age for participants, with the mean age of participants varying from 51.4 years [ 20 ] to 86.7 years [ 33 ], showing significant variations between the participants of the various studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies [ 18 , 38 ] did not report the age demographics of the study participants (although participants were adults). The remaining studies were conducted in adult patients (including but not exclusively elderly patients) [ 3 , 20 , 34 , 35 , 36 , 37 , 39 , 40 , 42 ]. The majority of the studies presented either the mean or median age for participants, with the mean age of participants varying from 51.4 years [ 20 ] to 86.7 years [ 33 ], showing significant variations between the participants of the various studies.…”
Section: Resultsmentioning
confidence: 99%
“…There were significant differences in the gender profiles for participants in the differing studies, with four studies [ 18 , 30 , 38 , 42 ] not reporting this characteristic; in the remaining fifteen studies, female participants represented 46%–72% of the sample populations, so there were significant differences between the study populations with regard to this, with differences also observed between those included in the development and individual validation studies carried out by the same researchers, e.g., females accounted for 49% of participants in the first validation study conducted by Kaufmann et al in 2018, compared to 61% of participants in the second validation study after the questionnaire was revised [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Drug-Associated Risk Tool (DART) is a 35-item questionnaire about risk factors deemed to be associated with DRPs. 16 The DART was developed to assist clinical pharmacists in stratifying their patients for medication reviews and to tailor clinical pharmacy services according to available resources. The items of the questionnaire were identified by triangulation, including quantitative and qualitative methods, described elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of the DART used as a self-administered questionnaire has been shown for hospitalised patients; compared with documented medical records, patients from geriatric, medical and orthopaedic wards with a median age of 81, 65 and 67.5 years, respectively, were able to adequately reproduce their medical information, limitations being renal and hepatic insufficiency. 16 …”
Section: Introductionmentioning
confidence: 99%